2007
DOI: 10.1063/1.2736290
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of blocking temperatures in nano-oxide layers of specular spin valves

Abstract: Articles you may be interested inInfluence of the domain structure of nano-oxide layers on the transport properties of specular spin valves Anomalous magnetoresistance behavior of CoFe nano-oxide spin valves at low temperatures J. Appl. Phys. 93, 7690 (2003); 10.1063/1.1540149Physical properties of spin-valve films grown on naturally oxidized metal nano-oxide surfaces Comparative study of magnetoresistance and magnetization in nano-oxide specular and nonspecular MnIr/CoFe/Cu/CoFe spin valves from 10 to 300 K S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Electrical resistance and magnetoresis-tance were measured with a standard four-point dc method, with a current stable to 1 : 10 6 and applied fields of up to 8 kOe and an automatic control and data acquisition system. Temperature dependent measurements were performed in a closed cycle cryostat down to 15 K. 32 To study the training effect, several experimental procedures were used. First, we performed field cooling runs ͑from 320 K͒ under different cooling fields H 0 ͑always applied along the MnIr/CoFe exchange bias direction͒.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical resistance and magnetoresis-tance were measured with a standard four-point dc method, with a current stable to 1 : 10 6 and applied fields of up to 8 kOe and an automatic control and data acquisition system. Temperature dependent measurements were performed in a closed cycle cryostat down to 15 K. 32 To study the training effect, several experimental procedures were used. First, we performed field cooling runs ͑from 320 K͒ under different cooling fields H 0 ͑always applied along the MnIr/CoFe exchange bias direction͒.…”
Section: Methodsmentioning
confidence: 99%
“…28 These NOL spin valves can more than double the MR ratio of simpler stacks because of specular reflection of electrons at the FM/NOL interfaces. 29 We recently showed that the pinned layer NOL is formed by CoFe oxides that have a paramagnetic/antiferromagnetic transition below room temperature ͑T B Ϸ 175 K͒ that can strongly affect transport properties, particularly MR. [30][31][32] In this work, we present a detailed study on the training effect in MnIr/CoFe/NOL/CoFe/Cu/CoFe/NOL/Ta specular spin valves by using MR͑H͒ measurements ͑in the 300-15 K temperature range͒ and different experimental procedures. The training effect was never observed in common nonspecular spin valves ͑without NOLs, but otherwise similar to the studied specular SV͒.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature-dependent measurements were performed in a closed cycle cryostat down to 20 K. 26,27 We define here the relative MTJ-resistance change ͑for parallel and antiparallel states͒ between 300 and 20 K as ␥ P,AP = ͑R 300 K P,AP − R 20 K P,AP ͒ / R 300 K P,AP , so that ␥ Ͻ 0 ͑Ͼ0͒ indicates tunnel-͑metallic-͒ like transport. 24…”
Section: Methodsmentioning
confidence: 99%
“…A gradual freezing of the interfacial frustrated spins at low T has been proposed as an explanation for the low-T sharp increase in the thermal variation in EB field, as observed in several F/AF bilayers. 5,[13][14][15] We believe that as a result of the spatial fluctuations in interfacial roughness and correlatively in frustration of exchange interactions across the F/AF interface, a distribution of J F/AF interfacial coupling also exists, which we write D͑J F/AF ͒. This other factor also contributes to the thermal dependence of exchange bias.…”
mentioning
confidence: 96%